THE INFLUENCE OF GOVERNMENT REGULATION NUMBER 46 OF 2013, TAXATION SOCIALIZATION AND QUALITY OF TAX SERVICE ON TAX OBLIGATION COMPLIANCE (Case Study of Taxpayers Registered at KPP Pratama Bandung Karees) - Yosi Febriani; Asep Kurniawan; Sri Mulyati (JABI (Journal of Accounting and Business Issues), 2019)
The aim of this research is to examine the influence of Government egulation Nomor 46 year 2013, socialization of taxation and service toward taxpayer compliance both partially and simultanly. This research ic conducted by giving the questionaires to all taxpayer in KPP Pratama Bandung Karees. Which is determined based on random sampling technique, so it is possessed 100 taxpayer. Analysis method used is double linier regression which use SPSS 20.0 tool. The results of the research are (1) implementing Government Regulation Nomor 46 year 2013 influences taxpayer compliance positively and signifantly, (2) socialization of taxation influences taxpayer compliance positively and signifantly, (3) the quality of tax service influences positively and signifantly of taxpayer compliance, (4) implementing Government Regulation Nomor 46 year 2013, socialization of taxation and service quality of tax affect taxpayer compliance positively and significantly.